The Efficiency Costs of Separating Carbon Markets Under the EU Emissions Trading Scheme: A Quantitative Assessment for Germany - Christoph Böhringer; Tim Hoffmann; Casiano Manrique de Lara Pe\~nate (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
From 1 January 2005 onwards the European Union has launched the first largescale international carbon emissions trading program. As the EU Emissions Trading Scheme (EU-ETS) covers only part of domestic carbon emissions, it implies a hybrid environmental regulation scheme: Each EU Member State must specify additional domestic abatement policies for the sectors that are not covered by the emissions trading scheme in order to meet its emissions budget under the EU Burden Sharing Agreement. Based on numerical simulations for Germany, we illustrate the efficiency drawback of hybrid carbon regulation which becomes particularly relevant when distributional constraints of the current EU-ETS design are taken into account.
Keywords: H21; Q48; D61; 330; emissions trading; hybrid regulation; National Allocation Plans; Emissionshandel; Kohlendioxid; Wirtschaftspolitische Wirkungsanalyse; EU-Staaten